Phytochemical analysis, antioxidative activity, cytotoxicity, and antimicrobial activity of two Vietnamese Camellia species: Camellia quephongensis and Camellia puhoatensis - Ninh The, Son; An Giang, Nguyen Thi; To Trang, Nguyen Thi; Huong, Le Thi; Minh Chau, Dao Thi; Khoa, Vu Van; Hoa, Nguyen Ngoc; Hop, Nguyen Quang; Dai, Do Ngoc (Vietnam Journal of Science and Technology, 2025)
Camellia quephongensis and C. puhoatensis are two Vietnamese perennial plants, which has engaged the attention due to their great values in beverage and pharmacology. For the first time, the phytochemical and biological evaluations of the ethanol extracts from the flowers and leaves of two Vietnamese Camellia species C. puhoatensis and C. quephongensis were carried out. Phytochemical screenings determined the appearance of flavonoids, tannins, saponins, free-reducing sugars, and polysaccharides. These ethanol extracts are promising antioxidants since they showed strong or better than the standard trolox in lipid peroxidation inhibition activity. These alcohol extracts were also superior to the positive control streptomycin in antimicrobial assays against the growth of Gram-positive bacterium Enterococcus faecalis ATCC299212 and Gram-negative bacteria Pseudomonas aeruginosa ATCC27853 and Salmonella enterica ATCC13076. In another approach, these extracts exhibited cytotoxicity towards seven cancer cell lines A549, HT-29, SK-Mel-2, HepG2, MCF-7, Hela, and MKN-7 at different levels of results. It needs to get more studies, focusing on the explanations by mechanism of actions